Highly transparent degradable hemicellulose-based polyurethane elastomer and preparation method and application thereof

CN122940973APending Publication Date: 2026-10-20GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611141349.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

目前行业内多采用高聚合度木聚糖、纤维素、木质素等大分子生物质对聚氨酯进行改性,此类原料分子内氢键缔合作用强,活性羟基易被分子链包裹屏蔽,反应活性偏低;实际应用中往往需要高掺杂量(10%以上)才能达到改性效果,不仅容易引发填料团聚、制品浑浊失透等问题,还会导致材料拉伸强度与断裂伸长率难以兼顾,力学性能失衡

Benefits of technology

[0020](1)本发明生物质原料结构适配光学材料,同步优化强韧性与透光性能。本发明选用木糖单元数为2~7的低聚合度木聚糖,分子链短小规整、分子内氢键作用力弱,大量表面活性羟基充分裸露,与聚氨酯基体相容性优异。仅微量添加即可和高分子长链二元醇构建协同交联网络,一方面提升体系交联密度与界面结合强度,显著提高拉伸强度;另一方面木聚糖表面羟基、醚键可与聚氨酯软段形成可逆动态氢键网络,材料受外力拉伸时,依靠分子链滑移、氢键重组耗散应力,在提升强度的同时完整保留高断裂伸长率,实现强度、韧性同步优化。同时该低聚木聚糖能够以单分子形式均匀分散在体系中,无纳米团聚、无微观相分离,保障制品本征高透光;而常规大分子生物质(高聚木聚糖、纤维素、木质素等)分子氢键密集,少量添加即易出现团聚浑浊,难以适配光学柔性材料。另外天然木聚糖多糖链段可向聚氨酯基体引入可降解结构,赋予材料优良生物降解特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a highly transparent, biodegradable hemicellulose-based polyurethane elastomer, its preparation method, and its applications. The polyurethane elastomer is prepared by copolymerization and crosslinking of long-chain diols, diisocyanates, low-polymerization-degree xylan, and a catalyst in an organic solvent. The low-polymerization-degree xylan has 2-7 xylose units and is added in dispersion or solution form. The number average molecular weight of the long-chain diol is not less than 1000. The resulting elastic material possesses excellent mechanical properties, high light transmittance, and biodegradability, overcoming industry shortcomings such as high filler content in existing biomass polyurethane processes, easy turbidity due to high-temperature reactions, cumbersome raw material pretreatment, and insufficient light transmittance. The overall formulation of this invention is mild, the process is simple, and the prepared elastomer possesses high optical transparency, balanced mechanical properties, and excellent biodegradability, making it suitable for various highly transparent, biodegradable flexible materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical-grade biodegradable biomass polyurethane elastomer technology, specifically relating to an oligoxylan-modified polyurethane elastomer, its segmented low-temperature preparation method, and its application in highly transparent flexible films. Background Technology

[0002] Polyurethane elastomers are high-molecular-weight polymers prepared by the polycondensation reaction of polyols and diisocyanates. Their molecular chains contain characteristic urethane bonds, resulting in high mechanical strength, wear resistance, aging resistance, and excellent elasticity. Currently, the raw materials for the synthesis of commercial polyurethanes mainly rely on petroleum-based polyols, which not only consumes non-renewable fossil resources but also results in finished products that are difficult to biodegrade naturally, leading to severe environmental pressure. Against this backdrop, utilizing natural biomass raw materials to replace some petroleum-based raw materials in the preparation of biomass-based polyurethanes has become an important research direction for the industry's low-carbon and sustainable development.

[0003] Xylan is a typical hemicellulose polysaccharide found in plant cell walls. Its main chain consists of D-xylose units linearly linked by β-1,4 glycosidic bonds. Rich in active hydroxyl groups, it can participate in polyurethane polymerization as a polyol component. Currently, the industry primarily uses high-polymerization-degree xylan, cellulose, lignin, and other macromolecular biomass to modify polyurethane. These raw materials exhibit strong intramolecular hydrogen bonding, and the active hydroxyl groups are easily shielded by the molecular chain, resulting in low reactivity. In practical applications, high doping levels (above 10%) are often required to achieve the desired modification effect. This not only easily leads to filler agglomeration and product opacity, but also makes it difficult to achieve a balance between tensile strength and elongation at break, resulting in an imbalance of mechanical properties. Furthermore, these macromolecular biomass typically require multiple pretreatment processes such as acid hydrolysis, ball milling, and chemical modification, resulting in complex processes, high production costs, and hindering large-scale production.

[0004] Existing hemicellulose-based polyurethane elastomers suffer from several drawbacks, including difficulty in achieving a balance between strength and toughness, poor interfacial compatibility, low crosslinking efficiency, and issues such as easy agglomeration of modified fillers, poor light transmittance, and weak biodegradability. Furthermore, most existing hemicellulose-modified polyurethanes are rigid insulating foams, whose formulations and molding processes are completely incompatible with high-transparency flexible films, making their application in such applications difficult. Summary of the Invention

[0005] The first objective of this invention is to provide a low-polymerization-degree xylan-based polyurethane elastomer; the second objective is to provide applications of this material.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] A highly transparent, biodegradable hemicellulose-based polyurethane elastomer is prepared by copolymerization and crosslinking of long-chain diols, diisocyanates, low-polymerization-degree xylan, and a catalyst in an organic solvent. The low-polymerization-degree xylan has 2-7 xylose units and is added in dispersion or solution form. The long-chain diol has a number-average molecular weight of not less than 1000. The surface of this low-polymerization-degree xylan is rich in active hydroxyl groups, which can form a synergistic crosslinking network with the long-chain diol. Under trace addition conditions, this simultaneously improves the tensile strength and elongation at break of the material, while also endowing the material with excellent optical transparency and biodegradability.

[0008] Preferably, a polyurethane prepolymer solution is obtained by reacting long-chain diols, diisocyanates and catalysts in an organic solvent, and then low-polymerization-degree xylan is added to continue the crosslinking reaction to obtain a highly transparent biodegradable hemicellulose-based polyurethane elastomer.

[0009] Preferably, the organic solvent is DMF (N,N-dimethylformamide), and the low-polymerization-degree xylan is added to the reaction system in the form of a DMF solution. The low-polymerization-degree xylan is a commercially available raw material that does not require pretreatment such as acid hydrolysis or ball milling and can be used directly.

[0010] Preferably, by mass, the raw materials include: 50-70 parts of long-chain diol, 10-30 parts of diisocyanate, 2-5 parts of low-polymerization-degree xylan, and 0.1-1 parts of catalyst; the amount of low-polymerization-degree xylan added is ≤8%.

[0011] Preferably, the amount of the low-polymerization-degree xylan added is ≤5%.

[0012] Preferably, the long-chain diol is a polyether diol, more preferably polytetrahydrofuran ether diol; the catalyst is selected from at least one of dibutyltin dilaurate, bismuth neodecanoate, and stannous octoate; the diisocyanate is selected from at least one of isophorone diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the molar ratio of hydroxyl groups in the long-chain diol, diisocyanate, and low-polymerization-degree xylan is 1:(1.1~1.5):1.

[0013] Preferably, the number-average molecular weight of the polyurethane elastomer is 40,000 to 50,000.

[0014] Preferably, the R value of the polyurethane elastomer is controlled at 1.1~1.5, the thickness is 0.1±0.05 mm, the film has a visible light transmittance of 600 nm ≥88%, and an ultraviolet transmittance of 400 nm ≥80%.

[0015] The preparation method of the highly transparent biodegradable hemicellulose-based polyurethane elastomer includes the following steps:

[0016] S1 Under a protective atmosphere (N2), the dehydrated long-chain diol is mixed with DMF organic solvent, diisocyanate and catalyst, and reacted at a constant temperature of 70±10℃ for 1.5~2.5 h to obtain a polyurethane prepolymer solution.

[0017] S2. The polyurethane prepolymer solution system is cooled to 50±5 ℃, and a low degree of polymerization xylan DMF dispersion with a dispersion concentration of 40~60 g / L is added. The mixture is stirred at a constant temperature of 50±5 ℃ for 1±0.5 h. The mixture is then poured into a mold and vacuum dried to obtain the finished product.

[0018] Application of the highly transparent biodegradable hemicellulose-based polyurethane elastomer in highly transparent flexible films.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The biomass raw material structure of this invention is adapted to optical materials, and the strength, toughness and light transmittance are optimized simultaneously. This invention selects low-polymerization degree xylan with 2 to 7 xylose units. The molecular chains are short and regular, the intramolecular hydrogen bonding is weak, and a large number of surface active hydroxyl groups are fully exposed, which has excellent compatibility with polyurethane matrix. Only a small amount of xylan can be added to form a synergistic crosslinking network with long-chain diols. On the one hand, it improves the crosslinking density and interfacial bonding strength of the system, and significantly improves the tensile strength. On the other hand, the hydroxyl groups and ether bonds on the surface of xylan can form a reversible dynamic hydrogen bond network with the soft segments of polyurethane. When the material is stretched by external force, it dissipates stress by relying on molecular chain slippage and hydrogen bond recombination. While improving the strength, it retains the high elongation at break, thus achieving simultaneous optimization of strength and toughness. Meanwhile, this oligoxylan can be uniformly dispersed in the system in the form of single molecules, without nano-agglomeration or micro-phase separation, ensuring the inherent high light transmittance of the product. In contrast, conventional macromolecular biomass (high-molecular-weight xylan, cellulose, lignin, etc.) has dense hydrogen bonds, and even small amounts can easily lead to agglomeration and turbidity, making it difficult to adapt to flexible optical materials. In addition, natural xylan polysaccharide segments can introduce biodegradable structures into the polyurethane matrix, endowing the material with excellent biodegradability.

[0021] (2) The segmented low-temperature process of the present invention can significantly improve the light transmittance of the material. At present, most biomass modified polyurethanes adopt a single high-temperature reaction system throughout the process; the segmented low-temperature process of the present invention (70°C prepolymerization, 50°C cooling reaction) can smoothly control the polymerization reaction rate of hydroxyl groups and isocyanates, avoid local burst polymerization caused by instantaneous violent reaction at high temperature, and generate micro cross-linked agglomerates, thereby reducing the haze of the film from the source and stabilizing the optical transparency performance; at the same time, it reduces the occurrence of high-temperature side reactions, making the molecular weight distribution of the product narrower and the performance uniformity better.

[0022] (3) The process of this invention is simple. The low degree of polymerization xylan used is a commercially available raw material. After purchase, it can be directly used to prepare DMF dispersion. There is no need for complex pretreatment processes such as acid hydrolysis, ball milling, and chemical degradation. The reaction conditions are mild and controllable, and it is green and environmentally friendly. In contrast, existing biomass raw materials all need to undergo long-term mechanical grinding, acid hydrolysis and other degradation treatments before they can be used. The process is lengthy and the energy consumption and processing costs are high.

[0023] (4) The filler addition amount of the present invention is low, which can avoid the problem of agglomeration and devitrification. The addition amount of low degree of polymerization xylan of the present invention can be as low as 5% or less, which can simultaneously improve the tensile strength and elongation at break of the material; existing biomass-based polyurethanes often require high filler content to play a modifying role, and at the same time, a large amount of biomass doping can easily aggravate the separation of matrix phase, causing the product to be turbid and the haze to increase, which cannot meet the requirements of high transparency materials. Attached Figure Description

[0024] Figure 1 The matrix-assisted laser desorption / ionization time-of-flight mass spectrum of the xylose units (2-7) xylan prepared in this invention.

[0025] Figure 2 Infrared spectra of xylo-oligosaccharides with different degrees of substitution and an R value of 1.3.

[0026] Figure 3 This is a light transmission effect diagram of the polyurethane elastomer prepared in Example 5.

[0027] Figure 4 The ultraviolet-visible light transmittance curves are shown for the polyurethane elastomers prepared in Example 5 and Comparative Example 7. Detailed Implementation

[0028] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any non-substantial modifications made by those skilled in the art based on the present invention fall within the scope of protection of the present invention.

[0029] The xylose units of the low degree of polymerization xylan used in this invention are 2-7, and were purchased from Anaiji (Shanghai) Pharmaceutical Chemical Co., Ltd.

[0030] Example 1

[0031] S1. Weigh 5.6 g of polytetrahydrofuran ether diol (number average molecular weight 2000), add it to a three-necked flask, and remove water under vacuum at 115-120 ℃ for 1.5 h. After the water removal is completed, cool down to 70 ℃.

[0032] S2. Under N2 protection, add 10 mL of DMF, 0.02 g of dibutyltin dilaurate, and 1.334 g of hexamethylene diisocyanate (R value 1.3) sequentially. Stir at 70 °C for 2 h to obtain a prepolymer solution.

[0033] S3. Cool the prepolymer system to 50 ℃, add all of the pre-prepared 0.5 g xylo-oligosaccharide / 20 mL DMF dispersion, stir and react at 50 ℃ for 1 h, pour into a mold and vacuum dry to obtain a transparent, non-agglomerated hemicellulose-based polyurethane elastomer.

[0034] Example 2

[0035] The only difference from Example 1 is that the amount of low-polymerization degree xylan added is changed to 0.4 g.

[0036] Example 3

[0037] The only difference from Example 1 is that an equimolar amount of diphenylmethane diisocyanate is used instead of hexamethylene diisocyanate.

[0038] Example 4

[0039] The only difference from Example 1 is that the amount of low-polymerization degree xylan added is changed to 0.2 g.

[0040] Example 5

[0041] The only difference from Example 1 is that the amount of low-polymerization degree xylan added is changed to 0.3 g.

[0042] Example 6

[0043] The only difference from Example 1 is that the number average molecular weight of the polytetrahydrofuran ether diol is 1000.

[0044] Example 7

[0045] The only difference from Example 1 is that the number average molecular weight of polytetrahydrofuran ether diol is 3000.

[0046] Example 8

[0047] The only difference from Example 5 is that the R value is 1.1.

[0048] Example 9

[0049] The only difference from Example 5 is that the R value is 1.2.

[0050] Example 10

[0051] The only difference from Example 5 is that the R value is 1.4.

[0052] Example 11

[0053] The only difference from Example 5 is that the R value is 1.5.

[0054] Comparative Example 1

[0055] The only difference from Example 5 is that low-polymerization-degree xylan is not added.

[0056] Comparative Example 2

[0057] The only difference from Example 5 is the addition of highly polymerized xylan (xylose units greater than 10).

[0058] Comparative Example 3

[0059] The only difference from Example 5 is the addition of 0.5 g of pure xylose.

[0060] Comparative Example 4

[0061] The only difference from Example 5 is that the xylo-oligosaccharide is not dispersed by dissolved DMF.

[0062] Comparative Example 5:

[0063] The only difference from Example 5 is that 1.5 g of xylo-oligosaccharide was added.

[0064] Comparative Example 6:

[0065] The only difference from Example 5 is that short-chain cellulose is used instead of xylo-oligosaccharides, and the S3 reaction temperature is 70 °C.

[0066] Preparation of short-chain cellulose: Dilute sulfuric acid is added to cellulose and stirred. The resulting mixture is then ball-milled until the short-chain cellulose is obtained.

[0067] Comparative Example 7:

[0068] The only difference from Example 5 is that short-chain cellulose (same as Comparative Example 6) is used instead of xylo-oligosaccharides.

[0069] Test metrics

[0070] According to GB / T528-2009 / ISO37:2005, the material was cut into a standard dumbbell shape and its tensile strength and elongation were tested at room temperature at a tensile rate of 100 mm / min.

[0071] Table 1 Test results of Examples 1-7

[0072]

[0073] Table 2 Test Results of Examples / Comparative Examples

[0074]

[0075] The test results of the samples in Examples 1-7 (different amounts of xylo-oligosaccharide) and Examples 8-11 (with R value adjusted from 1.1 to 1.5 based on Example 5) show that xylo-oligosaccharides with 2-7 xylose units can construct covalent cross-linking sites in the polyurethane system and form a reversible dynamic hydrogen bond network with the soft segments of the polyurethane. When the material is subjected to tensile force, it relies on the reversible recombination of hydrogen bonds and the synergistic dissipation of stress by polymer chain segment slippage to simultaneously improve tensile strength and elongation at break, thereby achieving a balanced optimization of strength and toughness.

[0076] Analysis of the R-value gradient (all adjusted based on the formulation of Example 5 with 0.3 parts xylo-oligosaccharide): The R-value represents the molar ratio of diisocyanate to the total hydroxyl groups in the system. When R=1.1, the supply of -NCO in the system is insufficient, the integrity of the crosslinking network is low, the crosslinking density is limited, and the tensile strength is only 24.3 MPa, but the elongation at break can reach 1210%, indicating outstanding toughness but weak strength. When R=1.2, the crosslinking reaction is more complete, the tensile strength is 33.6 MPa, the elongation at break is 1175%, and the overall mechanical properties are balanced. When the R-value is adjusted to 1.3, the matching degree of isocyanate with polyether diol and xylo-oligosaccharide hydroxyl groups is optimal, the covalent crosslinking sites are evenly distributed, there is no local hard segment enrichment, and the synergistic toughening effect of crosslinking network and dynamic hydrogen bonds reaches its peak, corresponding to the optimal tensile strength of 34.1 in Example 5. At MPa, the elongation at break was 1268%, and the film was transparent and free of haze throughout the process. Further increasing the R value to 1.4 increased the amount of residual free diisocyanate in the system, caused slight aggregation of local hard segments in micro-regions, and the tensile strength dropped to 31.1 MPa, while the elongation at break decreased to 1080%. When the R value was increased to 1.5, excess -NCO easily formed dense hard segment agglomerates, inducing micro-phase separation. The finished film showed a slight haze, and the elongation at break dropped sharply to 923%. Optical transparency and material toughness were simultaneously damaged.

[0077] Based on the content rules of xylo-oligosaccharides (Examples 1-5), the range of 0.2-0.5 parts of xylo-oligosaccharides added is the range with the best comprehensive performance. If too much xylo-oligosaccharides are added (Comparative Example 5, 1.5 parts added), the polysaccharide hydroxyl groups are enriched in large quantities, which can easily induce severe phase separation of the matrix, and the mechanical properties and light transmittance of the material will decrease significantly in tandem.

[0078] Compared to Example 5, the pure polyurethane matrix without added xylo-oligosaccharides in Comparative Example 1 had a tensile strength of only 15.3 MPa and an elongation at break of only 690%, significantly lower mechanical properties than Example 5 of this invention. This directly demonstrates that xylo-oligosaccharides have a significant cross-linking and toughening effect. Comparative Examples 2 and 3 changed the biomass raw materials: high-polymerization-degree xylo-oligosaccharides (xylose units > 10) have highly associated intramolecular hydrogen bonds, making them prone to aggregation in the matrix and causing film turbidity; single-molecule xylose has a single cross-linking site, easily leading to localized over-cross-linking and the generation of micro-scattering particles. The mechanical and light transmittance improvements of both were far weaker than those of 2-7 unit xylo-oligosaccharides. Comparative Example 4 directly added solid xylo-oligosaccharides without preparing a DMF dispersion, resulting in extremely poor raw material dispersion and a significant decrease in modification effect. This confirms that adding xylo-oligosaccharides in a DMF dispersion is a necessary process condition for achieving uniform dispersion of biomass single molecules and maintaining high light transmittance of the film.

[0079] Comparative Examples 6 and 7 were added as controls for cellulose-modified polyurethane: Comparative Example 6 used short-chain cellulose to replace xylo-oligosaccharides, and maintained a high-temperature reaction of 70 °C during the crosslinking stage. Under the same addition amount, the film was cloudy, with a visible light transmittance of less than 75% and a tensile strength of only 20.6 MPa. Comparative Example 7 replaced cellulose with the segmented low-temperature process of this invention. Although the haze of the film decreased slightly, the inherent defect of dense hydrogen bonds in the cellulose molecules could not be eliminated, and a large number of microscopic scattering particles still existed inside the matrix. The mechanical and light transmittance properties were still significantly inferior to the xylo-oligosaccharide system of this invention. This proves that the segmented low-temperature process alone cannot eliminate the aggregation defects of traditional macromolecular biomass. Only by combining the xylo-oligosaccharide raw materials in units 2-7 of this invention, the DMF dispersion feeding method, and the segmented low-temperature control process can the dual advantages of high mechanical strength and high light transmittance be achieved simultaneously.

[0080] Biodegradation tests after 60 days of soil burial showed that: the weight loss rate of the pure polyurethane sample without xylo-oligosaccharide in Comparative Example 1 was only 12.3%; the weight loss rates of cellulose-modified Comparative Examples 6 and 7 were only 21.7% and 26.5%, respectively, indicating low natural degradation rates; while the weight loss rate of the sample in Example 5, the optimal formulation of this invention, reached 60.1% after 60 days of burial, demonstrating significantly better degradation performance than all control groups. The mechanism is that the xylo-oligosaccharide molecules in units 2-7 are rich in β-1,4 glycosidic bonds and hydrophilic hydroxyl groups that can be decomposed by microorganisms, introducing numerous biodegradable sites into the polyurethane crosslinking network; the hydrophilic groups enhance the overall hydrophilicity of the material, facilitating the penetration of water and degradation enzymes secreted by soil microorganisms into the material interior; the xylo-oligosaccharide segments preferentially undergo enzymatic cleavage, disrupting the overall crosslinking framework; water molecules further attack the polyurethane urethane bonds, continuously breaking the chains, significantly improving the natural degradation ability of polyurethane, effectively addressing the industry's shortcoming of traditional petroleum-based polyurethane and cellulose-modified polyurethane being difficult to degrade.

[0081] from Figure 1Matrix-assisted time-of-flight mass spectrometry analysis of xylo-oligosaccharides, based on peak area and signal intensity weighting, showed that the average number of xylose units in the sample was 2, with the corresponding molecular weight concentrated in the range of 190-220 Da, confirming that the degree of polymerization of the raw materials used in this invention is within the design range.

[0082] Depend on Figure 2 Infrared spectroscopy revealed that all finished samples were within the range of 2200–2280 cm⁻¹. -1 The absence of the characteristic -NCO absorption peak at 1680–1700 cm⁻¹ indicates that the diisocyanate is fully involved in the copolymerization. -1 The significantly enhanced C=O stretching vibration peak of urethane confirmed that the hydroxyl groups of xylo-oligosaccharide and isocyanate underwent covalent cross-linking, indicating that the target polyurethane elastomer was successfully prepared.

[0083] Figure 4 The UV-Vis transmittance curves of polyurethane films modified with xylo-oligosaccharide (Example 5) and polyurethane films modified with cellulose (Comparative Example 7) at the same addition amount (3%) are shown. As can be seen from the curves, the 3% xylo-oligosaccharide-modified sample maintains a transmittance of over 85% in the entire visible light range of 400-800 nm, demonstrating excellent light transmittance. In contrast, the cellulose-modified sample with the same addition amount has a maximum visible light transmittance of only about 64%, significantly inferior to the xylo-oligosaccharide system. The root cause of the difference in transmittance lies in the dispersion and molecular aggregation behavior of the raw materials: cellulose molecular chains have dense hydrogen bonds, easily agglomerating in the polyurethane matrix to form micron-sized light-scattering particles, significantly blocking visible light transmission. This invention uses xylo-oligosaccharide with a degree of polymerization of 2-7, combined with dispersion feeding and a segmented low-temperature synthesis process, allowing polysaccharide molecules to be uniformly dispersed in the polyurethane cross-linked network without obvious agglomerated scattering phases. Therefore, the material can maintain high transparency while incorporating biomass modification and improving mechanical and biodegradable properties.

Claims

1. A highly transparent, biodegradable hemicellulose-based polyurethane elastomer, characterized in that, It is prepared by copolymerization and crosslinking of long-chain diol, diisocyanate, low-polymerization-degree xylan and catalyst in an organic solvent; the low-polymerization-degree xylan has 2 to 7 xylose units and is added in the form of dispersion or solution; the number average molecular weight of the long-chain diol is not less than 1000.

2. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 1, characterized in that, A polyurethane prepolymer solution is obtained by reacting long-chain diols, diisocyanates, and catalysts in an organic solvent. Then, low-polymerization-degree xylan is added to continue the crosslinking reaction, resulting in a highly transparent, biodegradable hemicellulose-based polyurethane elastomer.

3. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 2, characterized in that, The organic solvent is DMF, and the low-polymerization-degree xylan is added to the reaction system in the form of a DMF solution.

4. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 1, 2, or 3, characterized in that, The raw materials, by mass, include: 50-70 parts of long-chain diol, 10-30 parts of diisocyanate, 2-5 parts of low-polymerization-degree xylan, and 0.1-1 parts of catalyst; the amount of low-polymerization-degree xylan added is ≤8%.

5. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 4, characterized in that, The amount of the low-polymerization-degree xylan added is ≤5%.

6. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 5, characterized in that, The long-chain diol is a polyether diol, more preferably polytetrahydrofuran ether diol; the catalyst is selected from at least one of dibutyltin dilaurate, bismuth neodecanoate, and stannous octoate; the diisocyanate is selected from at least one of isophorone diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the molar ratio of hydroxyl groups in the long-chain diol, diisocyanate, and low-polymerization-degree xylan is 1:(1.1~1.5):

1.

7. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 1, 2, or 3, characterized in that, The number-average molecular weight of the polyurethane elastomer is 40,000 to 50,000.

8. The highly transparent biodegradable hemicellulose-based polyurethane elastomer according to claim 1, 2, or 3, characterized in that, The R-value of the polyurethane elastomer is controlled at 1.1~1.5, the thickness is 0.1±0.05 mm, and the transmittance of the film at 600 nm visible light is ≥88%, and the transmittance of the film at 400 nm ultraviolet light is ≥80%.

9. A method for preparing the highly transparent biodegradable hemicellulose-based polyurethane elastomer according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1 Under a protective atmosphere, the dehydrated long-chain diol is mixed with DMF organic solvent, diisocyanate and catalyst, and reacted at a constant temperature of 70±10℃ for 1.5~2.5 h to obtain a polyurethane prepolymer solution. S2. The polyurethane prepolymer solution system is cooled to 50±5 ℃, and a low degree of polymerization xylan DMF dispersion with a dispersion concentration of 40~60 g / L is added. The mixture is stirred at a constant temperature of 50±5 ℃ for 1±0.5 h. The mixture is then poured into a mold and vacuum dried to obtain the finished product.

10. The application of the highly transparent biodegradable hemicellulose-based polyurethane elastomer according to any one of claims 1 to 8 in highly transparent flexible films.